الفصيح المتروك في لهجة وادي ريغ - محمد, بن يحي (جامعة الوادي - University of Eloued, 2021)
يهدف هذا المقال إلى تسليط الضوء على بعض الألفاظ الفصيحة المتروك استعمالها في لهجة منطقة وادي ريغ (الجزائر)، وذلك بتأصيلها بالعودة إلى المعاجم العربية، والنصوص الفصيحة: القرآن الكريم، والحديث النبوي الشريف، وكلام العرب الفصحاء: شعره ونثره. Abstract: This article aims to highlight some eloquence words Abandoned or rarely used in Oued Righ (Algeria) dialect. We will rooting these words by referring it to ancient Arabic dictionaries, eloquent texts: the Holy Quran, The Hadith Sharif, and the ancient poetry and prose.
Keywords: الفصيح؛ المتروك؛ لهجة؛ وادي ريغ؛ الجزائر; Words eloquence; Abandoned; Dialect Oued Righ; Algeria